ANALYSIS OF COMMUNITY PARTICIPATION IN INFRASTRUCTURE DEVELOPMENT IN BULO-BULO VILLAGE, PUJANANTING DISTRICT, BARRU REGENCY - Nurlia (Sean Institute, 2022)
This study aims to determine: community participation in infrastructure development in Bulo-Bulo Village, Pujananting District, Barru Regency. The research method used is a qualitative research method. Data sources are primary data and secondary data. Data collection techniques were obtained by means of observation, interviews, and documentation. As well as data analysis techniques include the stages of data reduction, data presentation, and drawing conclusions. The results of this study indicate that community participation in infrastructure development in Bulo-bulo Village has been running quite well but not yet optimal, this is indicated by the lack of empowerment and community participation in realizing village development as desired by the community.